Penerapan Metode Fun Learning Untuk Meningkatkan Minat Belajar Al-Qur’an Peserta Didik di Pondok Tahfizh dan Tilawah Bayt El Hikmah Depok - Arsyad; Riam, Zaenal Abidin; Nufus, Hayatun (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2024)
This research aims to determine how much the fun learning method can increase students' interest in learning about the Al-Qur’an. This research uses a descriptive method. Data was obtained from Pondok Tahfizh and Tilawah Baye El Hikmah Depok students. The research method uses sampling techniques via random sampling, with data analysis using descriptive percentages. The research results show that the fun learning method can strengthen students' interest in learning the Al-Qur’an, with results based on indicators of learning interest, namely; (1) students show a happy attitude in participating in the learning process; (2) students are attentive in following the Al-Qur'an learning process; (3) students have a high desire to learn, by attending every day. Thus, using fun learning methods can create a more active and enjoyable learning process. The results of this research imply that to increase students' interest in learning, one thing teachers must do in the learning process is to use fun learning methods by creating a pleasant learning atmosphere so that students are interested in participating in the Al-Qur'an learning process.